Changes in Post-migration Living Difficulties Predict Treatment Outcome in Traumatized Refugees - Schick, Matthis (Front Psychiatry, 2018)
Background: Refugee mental health is affected by traumatic stressors as well as post-migration living difficulties (PMLD). However, their interaction and causal pathways are unclear, and so far, no distinct treatment recommendations regarding exile-related stressors exist. Methods: In a 3-year follow-up study, PMLD and symptoms of post-traumatic stress (PTS), depression and anxiety were examined in a clinical sample of severely traumatized refugees and asylum seekers (N = 71). Results: In regression analysis, reduction in PMLD predicted changes over time in depression/anxiety, but not in PTS. The opposite models with PMLD changes as outcome variable proved not significant for PTS, and significant, though less predictive, for depression/anxiety. Conclusions: In addition to well-established trauma-focused interventions for the treatment of PTS, psychosocial interventions focusing on PMLD might contribute to a favorable treatment response in traumatized refugees, particularly with regard to depression and anxiety.